2001
DOI: 10.1302/0301-620x.83b6.0830809
|View full text |Cite
|
Sign up to set email alerts
|

Scaphoid blood flow and acute fracture healing

Abstract: We have investigated whether assessment of blood flow to the proximal scaphoid can be used to predict nonunion in acute fractures of the scaphoid. We studied 32 fractures of the scaphoid one to two weeks after injury, by dynamic fat-suppressed T1-weighted gradient-echo MRI after the intravenous administration of gadopentetate dimeglumine (0.1 mmol/kg body-weight). Steepest slope values (SSV) and percentage enhancement values (%E) were calculated for the distal and proximal fragments and poles. All the fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…27 Others also found no correlation between proximal pole vascularity and nonunion. 28 29 The present study showed no significant difference in preoperative MRI.…”
Section: Discussioncontrasting
confidence: 51%
“…27 Others also found no correlation between proximal pole vascularity and nonunion. 28 29 The present study showed no significant difference in preoperative MRI.…”
Section: Discussioncontrasting
confidence: 51%
“…The systematic preoperative MRI was performed by only one author [ 18 ]. The previous studies have shown that MRI with contrast has failed to provide a correlation between vascularization and the presence of intraoperative punctate bleeding of the fragments [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%